Numerical Analysis of Buckling Behavior of Cold Formed Steel Angles With Intermediate Stiffener - Mutharasan, V.; Saranya, M.; Prabavathy, S. (AMC Indian Journal of Civil Engineering, 2018)
This project is mainly focused on the study of buckling behavior of cold formed steel angles. As column is a vertical compression member, it may affected by buckling, namely, local buckling, global buckling, torsional buckling, and distortional buckling. To enhance the buckling load capacity, the stiffeners were placed at the following positions : i) buckling axis ii) to connect the outer legs of the angle section iii) both buckling axis and the line connecting outer legs iv) triangular plate from corner to the buckling axis and v) triangular plate on the full cross section. In addition to that the length of columns are altered as 600 mm, 900 mm, and 1200 mm and the stiffener spacing as 100 mm, 150 mm, and 200 mm. Finite element analysis has been carried out by ANSYS Workbench 15.0 by creating the model using CATIA V5 software for the fixed ended cold formed equal angles with same thickness having five different sizes that makes the total number of specimens as 240. The column sections are analyzed by applying load on the top surface of the angle section. The analytical results obtained from FEM are compared with unstiffened column. By observing the results, it was found that the stiffener plate placed on the full section gives the better buckling load capacity compared to all others, but the stiffener provided at both the buckling axis and the line connecting outer legs fetches the optimum load capacity with economy in material and weld.